The Contribution of H. Mukhtar Gami Zebua in the Development of Islamic Education in Gunungsitoli - Ahmad Irfan Zebua; Azizah Hanum OK; Mohammad Al Farabi (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study aims to explore and analyze the contribution of H. Mukhtar Gami Zebua in the development of Islamic education in Gunungsitoli City, Nias Island. The background of this research is the reality that Gunungsitoli, a region with a Muslim minority population, has successfully established and developed Islamic educational institutions, largely due to the contributions of local figures such as Mukhtar Gami Zebua. The main focus of the research includes his biography, his role in da'wah and education, and the relevance of his contributions to the current condition of Islamic education. This research employs a descriptive qualitative method with a historical approach to Islamic education. Data collection techniques included document analysis, observation, and interviews with relevant informants. Data analysis was carried out based on historical analysis, content analysis, and contextual analysis , which were the combined into a crtitical historical synthesis, so that the final result is a conclusion and the relevance of the figure for the present. The findings reveal that H. Mukhtar Gami Zebua was a pioneer of modern Islamic education in Gunungsitoli. He founded and developed institutions such as Ibtidaiyah Muhammadiyah, SMP Muhammadiyah 32 Gunungsitoli, and the Aisyiyah Bustanul Athfal Kindergarten. He also played an active role in nurturing da’wah cadres and teachers, implementing an inclusive and contextual Islamic education system, and promoting Islamic values that are moderate, tolerant, and transformative. His legacy remains relevant today, particularly in fostering social harmony and strengthening Islamic identity through education.